Developing ˜Islam and Religious Moderation Course Based on Kampus Merdeka in Islamic Higher Education - Jamin, Ahmad; Mudra, Heri (Islam Realitas: Journal of Islamic and Social Studies, 2023)
The focus of the research is the development of the subject "Islam and Religious Moderation" in Islamic Education study program at IAIN Kerinci and learning tools, namely Rencana Pembelajaran Semester (RPS, Semester Learning Plan) and course syllabus. In conducting the research, the research and development (R&D) approach is used as a basic reference for developing lecture programs through observation or survey methods, trials and classroom actions. From the results and research analysis, it can be concluded that in the development of a course there are several things that must become the product of development including the course structure, RPS, syllabus, and course-teaching materials of course. In terms of the development of the Islamic and Religious Moderation course based on the Merdeka Belajar – Kampus Merdeka (MBKM, Independent learning – Independent campus) program, theoretical and practical analysis of the guidelines, instructions, and implementation of religious moderation and MBKM is needed. The product development courses are further refined through validation by curriculum and religious education experts and theoretical validation through journal articles of international repute as comparisons.